Analisis Kualitas Pelayanan Publik pada Kantor Kepala Desa Bulakwaru Kecamatan Tarub Kabupaten Tegal - Agus Susilo; Alfian Firmansyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The study uses a qualitative approach to examine the quality of public services at the Bulakwaru Village Head Office. This approach was chosen to gain a comprehensive and in-depth understanding of the dynamics and quality of the services provided. Data collection techniques include in-depth interviews with staff and service recipients, participant observation of the service process, and analysis of relevant documents. The research aims to measure and analyze the quality of services at the Bulakwaru Village Head Office, Tarub District, Tegal Regency, to identify factors affecting public satisfaction and provide recommendations for improving the quality of public services, particularly at the Bulakwaru Village Head Office. The study results indicate that while some elements of service are functioning well, several aspects need improvement, particularly in terms of speed and responsiveness. Recommendations from this study include staff training and facility improvements to support better service delivery. These findings are expected to assist stakeholders in developing strategies to enhance the quality of public services in this area.